Industrial valves : calculations for design, manufacturing, operation, and safety decisions - Sotoodeh, Karan (John Wiley & Sons, Inc., 2023)
"The book concentrates on modelling and calculations of some essential problems related to valves such as cavitation, corrosion, noise, and safety and reliability. Practical methods related to calculation of carbon dioxide corrosion, noise and water hammering are also included in this book. The book will be beneficial for professionals in various levels who are working with valves, actuators, material as well as mechanical engineers and advanced students studying this area. It contains real industrial examples as well as theoretical equations, calculations, and models"--